2020
DOI: 10.3390/rs12060954
|View full text |Cite
|
Sign up to set email alerts
|

Operational Large-Area Land-Cover Mapping: An Ethiopia Case Study

Abstract: Knowledge of land cover and land use nationally is a prerequisite of many studies on drivers of land change, impacts on climate, carbon storage and other ecosystem services, and allows for sufficient planning and management. Despite this, many regions globally do not have accurate and consistent coverage at the national scale. This is certainly true for Ethiopia. Large-area land-cover characterization (LALCC), at a national scale is thus an essential first step in many studies of land-cover change, and yet is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 106 publications
(80 reference statements)
1
14
0
1
Order By: Relevance
“…Much of the land is water-limited, with approximately 65% of the country occupied by drylands and only 15.1% of the total land considered arable, much of which is located within the drylands [45,46]. Figure 1 shows the elevation and distribution of land cover classified at a 30 m resolution [47]. The dominant classes present throughout the country include bare soil in the northwest, savanna in the eastern and western lowlands, and cropland in the highlands.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the land is water-limited, with approximately 65% of the country occupied by drylands and only 15.1% of the total land considered arable, much of which is located within the drylands [45,46]. Figure 1 shows the elevation and distribution of land cover classified at a 30 m resolution [47]. The dominant classes present throughout the country include bare soil in the northwest, savanna in the eastern and western lowlands, and cropland in the highlands.…”
Section: Study Areamentioning
confidence: 99%
“…The seasonal average maximum temperature was calculated at a pixel level, though no time lag was incorporated, and seasons correspond to those used for DP. Total rainfall, mean temperature, and mean NDVI were then extracted from pixels classified as vegetated land cover, based on the work of Khatami et al [47], for pixels where DP showed significant change. This process resulted in data from 1925 points for each year in the 17-year study period, which were further subset by pixels with significant positive and negative DP.…”
Section: Climatic Data and Spatial Panel Regression Modelsmentioning
confidence: 99%
“…The regional states and city administrations are further divided into Zones, Woredas (districts) and Kebeles (the smallest administrative unit) [102]. Agriculture is the backbone of the country's economy, accounting for 45% of the gross domestic product, 84% of the exports, and 80% of total employment [109,[113][114][115]. It has a highly diverse population with different religions, languages and ethnic groups [102,109].…”
Section: Country Profile and Demographymentioning
confidence: 99%
“…It has a highly diverse population with different religions, languages and ethnic groups [102,109]. Gross national per capita income remains at $850 United States Dollar in 2019 [116] despite the government pushing to reach lower-middleincome status by 2025 [115].…”
Section: Country Profile and Demographymentioning
confidence: 99%
“…However, this approach is still insufficient because it is difficult to continuously monitor long-term food threats, and it is even more difficult to trace the driving mechanism that causes food security problems. Ethiopia lacks specialized arable land data products to support its food security assessment [38]. It was not until the emergence of GFSAD African thematic arable land data in 2017 that this gap was filled [39].…”
Section: Challenges To Achieve Food Security Measuring and Resolvingmentioning
confidence: 99%